Using Online Discussion Forums to Enhance and Document Students' Workplace Learning Experiences: A Semi-Private Emirati University's Context - Semiyu Adejare Aderibigbe; Abdel Rahman Ahmed AbdelRahman; Hussain Al Othman (MDPI AG, 2023)
Workplace learning experience complements students' learning at the university and equips them with practical skills required in professional work contexts. Given its importance, educators must constantly devise strategies to enhance students' workplace learning and collect contextual data to determine how best to support them in collaboration with the internship sites. In this study, we adopted the online discussion forum to supplement undergraduate students' workplace learning in a semi-private Emirati university through reflection and workplace knowledge sharing with colleagues asynchronously. Using a qualitative approach, we ethically retrieved and thematically analyzed students' contributions to the online discussion forum. Our findings indicate that students found the orientation week beneficial and the knowledge gained at the university, such as communication and information technology, resourceful. Additionally, students found integration into the new context, time management, language issues, and emailing challenging. Despite the reported challenges, students indicated that the workplace learning experience strengthened their practical skills, including managing time, working with different people, and communicating within different contexts to smooth their transition to professional work contexts. Based on the findings, we suggest using online discussion to supplement workplace learning as an essential element for educators to consider when developing programs. We also recommend pre-internship orientations where expectations, roles, and required knowledge are discussed to prepare students for successful workplace learning experiences.